The impact of self compassion and emotion regulation on social anxiety in college students - Bahri, Marlistiani; Kholidin, Farid Imam; Yandri, Hengki (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Social anxiety is a common human experience, including among students. Social anxiety is a form of anxiety and fear of the judgment or views of other people. This research aims to reveal the influence of self-compassion and emotional regulation on social anxiety. This research uses quantitative research using survey and correlational designs. The subjects of this research were 159 IAIN Kerinci students. This research data was expressed using the Measuring the Scale and Scope of Social Anxiety among Students instrument, producing a Cronbach's Alpha of 0.939. The Short Form of the Self-Compassion Scale produced a Cronbach's Alpha of 0.779, The Difficulties in Emotion Regulation Scale: The DERS-16 produced a Cronbach's Alpha of 0.923, then the research results were processed using descriptive statistical analysis and hypothesis testing using simple and multiple regression techniques. The results of the analysis of the influence of self-compassion on social anxiety show a value of t = -5.447 with a significance value of 0.000. The second hypothesis which tested the influence of emotional regulation on social anxiety obtained a value of t = -9.373 with a significance value of 0.000, then testing using multiple regression obtained t = -.904 at a significance level of 0.367. Then t-count = -7.050 at a significance level of 0.000, then H0 is rejected, meaning the regression coefficient is significant. The research results showed that self-compassion and emotional regulation influence social anxiety. It is hoped that future researchers will reveal the influence of self-compassion and emotional regulation on social anxiety among students and society for a wider distribution.